2019
DOI: 10.15232/aas.2019-01887
|View full text |Cite|
|
Sign up to set email alerts
|

Invited Review: Nutritional regulation of gut function in dairy calves: From colostrum to weaning

Abstract: publicly funded repositories, such as the WHO COVID database with rights for unrestricted research re-use and analyses in any form or by any means with acknowledgement of the original source. These permissions are granted for free by Elsevier for as long as the COVID-19 resource centre remains active. ABSTRACTPurpose: Published literature regarding calf nutrition was reviewed to create an information base for the implementation of proper nutritional management to maximize health and productivity.Sources: The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 127 publications
1
26
0
1
Order By: Relevance
“…It is now recommended to feed calves higher milk allowances for increased productivity and growth [18][19][20]. From the perspective of a high first lactational yield, the optimal prepubertal average daily weight gain of Norwegian Red cattle is estimated to 890 g/d [21].…”
Section: Resultsmentioning
confidence: 99%
“…It is now recommended to feed calves higher milk allowances for increased productivity and growth [18][19][20]. From the perspective of a high first lactational yield, the optimal prepubertal average daily weight gain of Norwegian Red cattle is estimated to 890 g/d [21].…”
Section: Resultsmentioning
confidence: 99%
“…Important advantages of feeding higher milk allowances are related to the prevention of hunger (De Paula Vieira et al, 2008), a feeding pattern more consistent with the natural behavior of calves (Appleby et al, 2001), and higher preweaning growth rates (Jasper and Weary, 2002). It is now recommended that calves should be fed higher milk allowances for increased productivity and growth (Geiger et al, 2016;Fischer et al, 2019). In fact, recent meta-analyses have indicated that average daily gain preweaning is positively correlated with first lactational milk yield in adult life (Soberon and Van Amburgh, 2013;Gelsinger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An elevated plane of nutrition in the very beginning month leads into a greater productivity and growth. This is because colostrum and transition milk comprise a plenty of bioactive molecules that favors gut development and microbiota as well [32]. However, a transition from liquid pre-weaned feed to solid weaned calf feed needs to done carefully to reduce dietary stress and reduce morbidity [5,33].…”
Section: Feeding Managementmentioning
confidence: 99%